2021
DOI: 10.1177/01939459211062956
|View full text |Cite
|
Sign up to set email alerts
|

A Landscape of Subjective and Objective Stress in African-American Dementia Family Caregivers

Abstract: Stress is a significant part of daily life, and systemic social inequities, such as racism and discrimination, are well-established contributors of chronic stress for African Americans. Added exposure to the stress of caregiving may exacerbate adverse health outcomes. This secondary analysis describes subjective and objective stress in African American family caregivers, and relationships of subjective and objective stress to health outcomes. Baseline data from 142 African American dementia family caregivers f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…In a nationally representative study, 428 Black and Hispanic participants had poorer health prior to becoming a caregiver for a spouse with dementia than those of similar race/background who did not become caregivers; such differences were not apparent among White caregivers. Discrimination is also linked with depressive symptoms among African American dementia caregivers 429 …”
Section: Caregivingmentioning
confidence: 99%
See 1 more Smart Citation
“…In a nationally representative study, 428 Black and Hispanic participants had poorer health prior to becoming a caregiver for a spouse with dementia than those of similar race/background who did not become caregivers; such differences were not apparent among White caregivers. Discrimination is also linked with depressive symptoms among African American dementia caregivers 429 …”
Section: Caregivingmentioning
confidence: 99%
“…Discrimination is also linked with depressive symptoms among African American dementia caregivers. 429 Existing research also suggests nuanced findings related to racial and ethnic differences in dementia caregiving. For example, Black caregivers are more likely than White caregivers to report positive aspects of caregiving.…”
Section: Caregiving and Womenmentioning
confidence: 99%
“…Covid stress also failed to demonstrate an association with any of the measured sleep variables. These findings were unexpected as many of the initial studies examining sleep reported a disruptive effect of the pandemic (Partinen, 2021), with chronic stress previously demonstrating reliable associations with sleep disruption (Cothran et al, 2022). However, such results are not replicated across every study.…”
Section: Discussionmentioning
confidence: 80%
“…Evidence shows that telephone-based programs are effective alternatives to in-person support programs (Cothran et al, 2021; Greenberg et al, 2020; Hwang et al, 2021; Kasar & Karaman, 2021; Mok et al, 2020; Sitges-Macia et al, 2021). More so, in the early pandemic, many caregivers were unfamiliar with web-based interfaces such as Zoom or Google Meet, which would have allowed for camera accessibility.…”
Section: Discussionmentioning
confidence: 99%